2004
DOI: 10.1063/1.1788883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti–W codoping on the optical and electrical switching of vanadium dioxide thin films grown by a reactive pulsed laser deposition

Abstract: Thin films of thermochromic VO2, V1−xWxO2 and V1−x−yWxTiyO2 (x=0.014, and y=0.12) were synthesized onto quartz substrates using a reactive pulsed laser deposition technique. The films were then characterized by x-ray diffraction and x-ray photoelectron spectroscopy. The W and Ti dopant effects on the semiconductor-to-metal phase transition of VO2 were investigated by measuring the temperature dependence of their electrical resistivity and their infrared transmittance. Remarkably strong effects of Ti–W codoping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(101 citation statements)
references
References 18 publications
2
93
0
1
Order By: Relevance
“…Moreover, the co-doped films had a smaller ∆T MI compared with the nondoped film. 16 are also plotted for comparison. It is well known that hole doping by lower-valence elements such as Cr 3+ or Al 3+ raises the T MI , whereas electron doping with higher-valence elements such as Nb 5+ or W 6+ lowers the T MI .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the co-doped films had a smaller ∆T MI compared with the nondoped film. 16 are also plotted for comparison. It is well known that hole doping by lower-valence elements such as Cr 3+ or Al 3+ raises the T MI , whereas electron doping with higher-valence elements such as Nb 5+ or W 6+ lowers the T MI .…”
Section: Resultsmentioning
confidence: 99%
“…However, Soltani et al reported that co-doping of VO 2 with Ti and W suppresses thermal hysteresis more effectively than does doping with W alone. 16 In their study, they simultaneously achieved a practical absence of thermal hysteresis and a TCR of 5.12%/K at room temperature in V 0.866 W 0.014 Ti 0.12 O 2 films. This TCR is larger than that of conventional uncooled bolometer materials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the value of T t can be decreased to room temperature by judiciously controlling the W doping concentration. Furthermore, the optical and electrical hysteresis can be completely eliminated by co-doping VO 2 with W and Ti [2]. The SMT characteristics of VO 2 can thus be exploited in various technological applications including all-optical switches, electro-optical switches, uncooled IR microbolometers, smart windows, etc.…”
Section: Introductionmentioning
confidence: 99%
“…M. Soltani et al reported the optical and electrical properties of Ti-W co-doped VO 2 thin films by the PLD method. 21 However, PLD method is improper for growing large-size samples. Meanwhile, the deposition temperature is commonly very high at ~520 o C, which is not compatible to semiconductor techniques.…”
Section: Introductionmentioning
confidence: 99%